Assessing drug consumption in Kuantan, Pahang, Malaysia, through the wastewater-based drug epidemiology (Wbde) approach - Mohammad Azimuddin, Izani; Nurul `Azyyati, Sabri; Khaw, Kooi Yeong; Iekhsan, Othman; Tay, Joo Hui (AIP Publishing, 2025)
This study utilized a wastewater-based drug epidemiology (WBDE) approach to estimate illicit drug consumption in the selected communities of Kuantan, Pahang, Malaysia. Raw wastewater samples (24-h composite) were collected from fourteen local wastewater treatment plants (WWTPs) between August to November 2021. The concentrations of five illicit drugs, namely 3,4-methylenedioxymethamphetamine (MDMA), 3,4-methylenedioxyamphetamine (MDA), amphetamine (AMP), methamphetamine (METH) and morphine (MOR) were analyzed using liquid chromatograh with tandem mass spectrometry (LC-MS/MS). AMP, METH, MDMA and MDA were detected at concentrations ranging from below detection limit (<LOD) to 1890 ng/L, whereas MOR was not found in all samples. Results revealed that METH was the most prevalent substance having the highest detection frequency (DF = 96.4%), followed by MDA (DF 58.9%) and AMP (DF 26.8%). Estimation of drug consumption was performed using back-calculation method and the results showed that METH was the most widely used illegal substance in Kuantan District, with an estimated mean consumption rate of 7.04 mg/day/1000 individuals.